Primary sources control the variability of aerosol optical properties in the Antarctic Peninsula. Issue 1 (1st January 2018) - Asmi, Eija; Neitola, Kimmo; Teinilä, Kimmo; Rodriguez, Edith; Virkkula, Aki; Backman, John; Bloss, Matthew; Jokela, Jesse; Lihavainen, Heikki; de Leeuw, Gerrit; Paatero, Jussi; Aaltonen, Veijo; et al.
Abstract: Aerosol particle optical properties were measured continuously between years 2013–2015 at the Marambio station in the Antarctic Peninsula. Annual cycles of particle scattering and absorption were studied and explained using measured particle chemical composition and the analysis of air mass transport patterns. The particle scattering was found elevated during the winter but the absorption did not show any clear annual cycle. The aerosol single scattering albedo atλ = 637  nm was on average 0.96± 0.10, with a median of 0.99. Aerosol scattering Ångström exponent increased during summer, indicating an increasing fraction of fine mode particles. The aerosol was mainly composed of sea salt, sulphate and crustal soil minerals, and most of the particle mass were in the coarse mode. Both the particle absorption and scattering were increased during high wind speeds. This was explained by the dominance of the primary marine sea-spray and wind-blown soil dust sources. In contrast, the back-trajectory analysis suggested that long-range transport has only a minor role as a source of absorbing aerosol at the peninsula.